Not just bricks and mortar: planning hospital cancer services for Aboriginal people - Thompson, Sandra; Shahid, Shaouli; Bessarab, Dawn; Durey, Angela; Davidson, Patricia (BioMed Central Ltd, 2011)
Background: Aboriginal people in Australia experience higher mortality from cancer compared with non- Aboriginal Australians, despite an overall lower incidence. A notable contributor to this disparity is that many Aboriginal people do not take up or continue with cancer treatment which almost always occurs within major hospitals. Thirty in-depth interviews with urban, rural and remote Aboriginal people affected by cancer were conducted between March 2006 and September 2007. Interviews explored participants’ beliefs about cancer and experiences of cancer care and were audio-recorded, transcribed verbatim and coded independently by two researchers. NVivo7 software was used to assist data management and analysis. Information from interviews relevant to hospital services including and building design was extracted. Findings: Relationships and respect emerged as crucial considerations of participants although many aspects of the hospital environment were seen as influencing the delivery of care. Five themes describing concerns about the hospital environment emerged: (i) being alone and lost in a big, alien and inflexible system; (ii) failure of open communication, delays and inefficiency in the system; (iii) practicalities: costs, transportation, community and family responsibilities; (iv) the need for Aboriginal support persons; and (v) connection to the community. Conclusions: Design considerations and were identified but more important than the building itself was the critical need to build trust in health services. Promotion of cultural safety, support for Aboriginal family structures and respecting the importance of place and community to Aboriginal patients are crucial in improving cancer outcomes.